Post-conflict Sri Lanka from Human Security Perspective - Padmakumara, S.C (My University, 2011)
Today, in a broader sense, Security has become one of dominant component that shapes the international system, not the least at national level. The end of the Cold War has created specific academic discourses over the meaning of security and its conceptualization as a field of enquiry. The studies of security from traditional view, emphasizing components such as responding to anarchy and maintaining national security through military entities -are becoming obsolete as contemporary literature on security speaks to a broader sense along multi-dimensional frameworks. In recent years, the concept of „Human Security‟ based on people-centered model of security, has become a fresh approach to security studies. As defined by the United Nations Human Development Report, “Human Security includes safety from chronic threats such as hunger, disease and repression as well as protection from sudden and harmful disruptions in the pattern of daily life” (1994:23). The major objective of this paper is to examine how the concept of Human Security can be utilized in a post- conflict situation with special reference to Post Conflict Sri Lanka. Furthermore, the paper will distinguish the traditional security from the Human Security, focusing on its distinct dimensions such as Individual, Community, Environmental, Food, Health and Economic Security. As archival based study, this will provide series of suggestions to be met in the agenda of the post- conflict development process in Sri Lanka to make it more effective in addressing non-military issues.